Improving SCOBY starter using co-culture of tapai and bakery yeast - Aurora Urbahillah; Jay Jayus; NURHAYATI NURHAYATI (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Urbahillah A, Jayus J, Nurhayati N. 2021. Improving SCOBY starter using co-culture of tapai and bakery yeast. Biodiversitas 22: 4617-4624. Kombucha is a beverage fermented by a symbiotic bacteria and yeast known as SCOBY (Symbiotic Culture of Bacteria and Yeast). Bacteria and yeast contribute to the formation of organic acids, aroma, taste, and flavor of kombucha. The commercial yeasts used in Indonesian are baker’s yeast and tapai yeast. This study was conducted to develop SCOBYco-culture with tapai yeast and baker’s yeast and evaluate its activity. The ingredients for the kombucha were cascara, water, and sugar, which were fermented with three formula starter, i.e. original SCOBY 10% w/v (SN), co-culture SCOBY 10% w/v with 0.1% w/v of baker’s yeast (SNR), and co-culture SCOBY 10% w/v with tapai yeast 0.1% w/v (SNT). The starter activity were determined based on the OD (Optical Density) value. Yeast screening was carried out on the dominant starter population. Furthermore, morphologically yeast was identified based on colony type, color, and shape of cell. Then yeast was identified by their fermentation profile using API 20C Aux Kit. Isolate A showed white colony with convex elevation and the cell was round-shaped. Colony of isolate B and isolate C were creamy in color and oval cell shaped. The API results revealed that the first isolate was identified as Candida famata, second isolate was as Candida krusei, and the third isolate was as Candida magnoliae. Three types of fungi were found from SCOBY, namely Mucor sp., Trichoderma sp., and Fusarium sp. Mucor sp. has non-septate hyphae, and round black spores. Trichoderma sp. has septate hyphae, greenish-white spores, and the conidia have the shape of globose to ellipsoidal Fusarium sp. has a mold with septate hyphae, yellowish-white colonies, and the conidia have the shape of obovoid. Bacteria, yeast, and mold present in the medium form a powerful symbiosis for produce metabolite.